Edukasi Hipertensi dan Terapi Komplementer Rebusan Daun Salam pada Lansia di Desa Carebbu Kec. Awangpone Kab. Bone - A. Artifasari; Irawati, Irawati (Jurnal Pengabdian Masyarakat, 2025)
Hypertension is a common health problem among the elderly and is a major risk factor for various cardiovascular diseases. Efforts to reduce the incidence of hypertension rely not only on pharmacological therapy but also on non-pharmacological therapies as support. One non-pharmacological method that can be used is the use of boiled bay leaves, which are known to contain active compounds such as flavonoids and essential oils that have the potential to help lower blood pressure. This community service activity aims to increase the elderly's knowledge about the benefits of complementary therapy, specifically the consumption of boiled bay leaves as an independent effort to control blood pressure. The community service was carried out through a health education activity on October 28, from 2:00 PM to 3:00 PM WITA in the Carebbu Village Office Hall, Awampone District, Bone Regency. Participants were elderly people who were present and willing to participate in the series of activities. The activity implementation included filling out an attendance list and pre-test questionnaire, providing materials by the community service team, completing a post-test, and free blood pressure checks. The results of the activity showed an increase in the elderly's knowledge about complementary therapy and the importance of managing hypertension independently or with the support of health workers.